Analysis of the Cytotoxic Effects of Eryngium billardieri Delar. Extracts on MCF7 Cell Line - Leyla Paşayeva; Esra Köngül; Rojen Geylan; Gökçe Şeker Karatoprak; Osman Tugay (Proceedings, 2017)
The Apiaceae (previously known as the Umbelliferae) is one of the largest plant families in the world. This family comprises approximately 450 genera and 3700 species worldwide. The members of this family are well known as vegetables, culinary and medicinal plants. Members of Apiaceae possess various compounds with many biological activities. Some of the main properties are ability to induce apoptosis, antibacterial, hepatoprotective, vaso-relaxant, cyclooxygenase inhibitory and antitumor activities. In this study, 70% methanol extract prepared from the aerial parts of Eryngium billardieri, which belongs to Apiaceae family, and ethyl acetate, n-butanol fractions obtained from this extract were investigated by MTT method for cytotoxic effect on MCF7 (human breast cancer cell line) cell line. In result, the methanol extract was found more cytotoxic than fractions with 99.50 µg/mL IC50 value on MCF7 cell line.